Ekonomi negeri Kelantan dari perspektif analisis shift-share wilayah - Abdul Rashid, Zakariah (Universiti Putra Malaysia Press, 2003)
Using regional shift-share analysis the present study, covering the overall period of 1980-95 which is subdivided into two sub-periods, aims at analysing the performance of Kelantan's economy vis-a-vis national economy. The state GDP data according to its major sectors are collected from EPU and the state EPU which is expressed in its real value by using GDP deflator. The results show that to investors the state is unattractive locationally, good performance of national industrialisation stimulates that of the state, and its advantage in primary sector is erroded because of structural change at the national level. The study offers few policy recommendations.